Gravitropism and mechanical signaling in plants1. Issue 1 (1st January 2013) - Toyota, Masatsugu; Gilroy, Simon
Abstract : Mechanical stress is a critical signal affecting morphogenesis and growth and is caused by a large variety of environmental stimuli such as touch, wind, and gravity in addition to endogenous forces generated by growth. On the basis of studies dating from the early 19th century, the plant mechanical sensors and response components related to gravity can be divided into two types in terms of their temporal character: sensors of the transient stress of reorientation (phasic signaling) and sensors capable of monitoring and responding to the extended, continuous gravitropic signal for the duration of the tropic growth response (tonic signaling). In the case of transient stress, changes in the concentrations of ions in the cytoplasm play a central role in mechanosensing and are likely a key component of initial gravisensing. Potential candidates for mechanosensitive channels have been identified in Arabidopsis thaliana and may provide clues to these rapid, ionic gravisensing mechanisms. Continuous mechanical stress, on the other hand, may be sensed by other mechanisms in addition to the rapidly adapting mechnaosensitive channels of the phasic system. Sustaining such long‐term responses may be through a network of biochemical signaling cascades that would therefore need to be maintained for the many hours of the growth response once they are triggered. However, classical physiological analyses and recent simulation studies also suggest involvement of the cytoskeleton in sensing/responding to long‐term mechanoresponse independently of the biochemical signaling cascades triggered by initial graviperception events.